Academic writing : Citation is troublesome and plagiarism is no big deal - Ting, Su Hie (Universiti Malaysia Sarawak, UNIMAS, 2013)
The study examined the seriousness of plagiarism in university students’ written assignments. The specific objectives of the study were to: (1) identify the plagiarism behaviours used by students to complete their written assignments; (2) determine students’ attitudes towards penalties of plagiarism; and (3) determine reasons for the occurrence of plagiarism. Questionnaires were distributed to students enrolled in an academic reading and writing course at a non-research intensive Malaysian university. Analysis of 169 questionnaires showed all the students had been involved in some plagiarism behaviours to complete their assignments, primarily use of materials without properly acknowledging the source of the information. The students did not treat plagiarism as a serious act of academic dishonesty as shown by their preference for light penalties for students caught for plagiarism. It seems that the students’ lack of awareness on the severity of plagiarism may be due to the lack of emphasis on inclusion of citations in assignments by lecturers. The findings suggest that it is not enough to teach students the conventions of citation and referencing but they need to be educated on the practices of academia, particularly pertaining to research, publications and academic honesty in use of materials.